Expression of WW domain‐containing oxidoreductase and its clinical implication in endometrial adenocarcinoma patients with metabolic syndrome. Issue 1 (25th February 2021) - Shen, Yan; Gao, Leilei; Jiang, Shanshan; Liu, Jinwei; Cheng, Weiye; Shou, Huafeng
Abstract: Aim: Metabolic syndrome (MS) is tightly associated with the oncogenesis and prognosis of endometrioid adenocarcinoma, but the underlying mechanism is unclear. Here, we studied the relation between the expression status of WW domain‐containing oxidoreductase (WWOX) and the clinicopathological features of endometrioid adenocarcinoma patients with MS. Methods: Fifty‐seven samples of endometrial adenocarcinoma were chosen for detection of expression level of WWOX. Overall survival (OS) time of these patients was analyzed by univariate and multivariate analysis. Survival analysis of patients with different WWOX expression levels from the Cancer Genome Atlas (TCGA) database was also performed. Results: The WWOX expression is significantly higher in MS group than that in non‐MS group (36.4% vs 65.7%, P = .03). WWOX was closely related to MS ( P = .03) and muscle invasion of tumor cells ( P = .04), but age, tumor grade, status of lymphatic metastasis, and FIGO (International Federation of Gynecology and Obstetrics) stage were not significantly different between the two WWOX expression status. Univariate analysis revealed that lymphatic metastasis ( P = .023) and lower stage ( P = .006) are significantly associated with OS. Multivariate analysis demonstrated that stage was an independent prognostic factor for OS (hazard ratio = 0.197; 95% CI, 0.043‐0.896). Downregulation of WWOX was statistically associated with OS in patients from TCGA database ( P = .04). Conclusion: WWOX may play an important role in the progression of endometrial cancer with MS. Abstract : WWOX expression was significantly lower in endometrial adenocarcinoma patients with metabolic syndrome (MS). Clinical analysis revealed WWOX was associated with muscle invasion and downregulation of WWOX was associated with overall survival. It is suggested that WWOX may play an important role in the progression of endometrial cancer with MS.